Synthesis and Characterization of Poly(styrene)-block-Poly(acrylic acid) and Organoclay Based Hybrid Composite Materials - Soomro, S. H.; Sanaullah, M.; Zaman, N.; Laghari, A. Q.; Jalbani, N. B.; Mirza, K.; Abbasi, E. A. (Engineering, Technology & Applied Science Research, 2018)
Abstract—Polystyrene (PS) and polyacrylic acid (PAA) are organic and synthetic polymers. Generally, a composite needs a matrix and reinforcement. Montmorillonite (MMT) is used as reinforcement to form a hybrid matrix by ultra-sonication. Block polymers of PS and PAA were first synthesized and then hybrid nanocomposite material of synthesized block polymeric matrix was fabricated by incorporating organoclay as reinforcement through 6 and 12 hours of ultra-sonication. The characterizations of the hybrid nanocomposite material were done by UV-visible and infrared (IR) spectroscopy, which confirm the successful synthesis of PS and PAA block polymer. The UV-visible spectroscopic measurements revealed that hybrid composite material is different from PS-block-PAA and that absorbance increases on increasing concentration. After successful ultra-sonication the hybrid composite is analyzed through scan electron microscopy (SEM) regarding surface morphology, distribution, uniformity, porosity, matrix compatibility, and matrix reinforcements. Sonication (for 6 hours) demonstrates a heterogeneous porous surface and an increase in roughness and porosity of surface morphology at different optical zooms.